Association Between Children’s Theory of Mind and Responses to Insincere Praise Following Failure - Mizokawa, Ai (Frontiers in Psychology, 2018)
This study examined children’s interpretations of and responses to insincere praise in a situation involving failure and explored the association between these responses and the maturity of their theory of mind. Seventy-two young Japanese children (mean age = 5.70 years, SD = 0.61) completed a test battery that included tasks designed to assess responses to teacher feedback (i.e., insincere praise, no feedback) in hypothetical failure situations, theory of mind, and verbal ability. The results showed that children who failed experienced higher levels of positive emotion and self-rated performance and showed lower motivation to persevere when they received insincere praise following failure, relative to those observed when they failed and received no feedback. In addition, relative to children with less mature theory of mind, children with mature theory of mind responded more negatively to insincere praise following failure. The evidence indicated that the effects of insincere praise could differ according to the maturity of children’s theory of mind. It highlights the importance of understanding individual differences in theory of mind in parenting and educational settings.